Measuring empowerment in patients with chronic disease: psychometric qualities of the Portuguese Rheumatic Disease Empowerment Scale - Alves, Marta Pereira (2021)
ABSTRACT - Empowerment is usually defined as a process of promoting the sense of competence and control as a means of capacitating individuals to improve their life conditions. The aim of this study was to describe the psychometric qualities of the Portuguese Rheumatic Disease Empowerment Scale (PRES- 8), an 8-item measure of empowerment for patients with rheumatic disease. The study enrolled 81 patients with rheumatic diseases. Participants filled in the P-RES-8, the Portuguese validated version of the Medical Outcomes Survey Short Form-36 (MOS SF-36), and a questionnaire including sociodemographic data and disease-related variables. To evaluate the dimensionality of the P-RES-8 scale, an exploratory factor analysis was conducted, and its reliability was assessed by Cronbach’s α. The validity of this measure was assessed by analyzing the correlations between empowerment, quality of life, and other relevant variables (education level and illness duration). The P-RES-8 proved to be a reliable 1-dimensional measure of empowerment in patients with rheumatic disease (Cronbach’s α = 0.94). Empowerment was positively related to quality of life. Particularly, the findings showed positive associations between empowerment, assessed by the P-RES-8, and each of the 8 domains of the MOS SF-36. The associations were stronger for mental health and general health perception. The results also revealed that empowerment is positively associated with a higher education and more years after the diagnosis. The findings provide support for the adequacy of the P-RES-8 as a measure of empowerment in patients with rheumatic disease. Moreover, empowerment showed to be an important variable in the assessment of patients’ quality of life.